Supporting Factors Affecting Area Development at the Special Economic Zone Border, Mukdahan Province - Natnaporn Eaknarajindawat (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Province of Mukdahan has been considered to be a Special Economic Development Zone due to its location being one of Thailand’s major trade border. This leads to the intention to study supporting factors affecting the development of the Special Economic Zone area by collecting data from 20 crucial participants and 400 sample groups, adopting the principle of 20 ties ratio of the controlled experiment and the method of selecting target samples according to portion. Results found, after specifically considering the factors that have direct effect on the development of the Special Economic Zone area of Mukdahan province, that public participation by the people alone will have direct effect on the development of the Special Economic Zone area of Mukdahan province at 0.67 percent while tools support the effect on Special Economic Zone and the management system has indirect effect on the development of the Special Economic Zone area of Mukdahan province at 0.67 percent, 0.46 percent and 0.45 percent respectively.